Extração de metais (K, Mg, Ba, Ca, Cr, Mn, Li, Fe) de água produzida utilizando sistema microemulsionado - Nascimento, Yasmine ísis Fernandes do (2014)
The produced water is a byproduct formed due to production of petroleum and carries with it a high amount of contaminants such as oil particles in suspension, organic compounds and metals. Thus, these latter pollutants are very difficult to treat because of its high solubility in water. The objective of this work is to use and evaluate a microemulsioned system to remove metals ( K , Mg , Ba , Ca , Cr , Mn , Li , Fe ) of synthetic produced water. For the extraction of metals, it was used a pseudoternary diagram containing the following phases: synthetic produced water as the aqueous phase (AP), hexane as organic phase (OP), and a cosurfactant/surfactant ratio equal to four (C/S = 4) as the third phase, where the OCS (saponified coconut oil) was used as surfactant and n-butanol as cosurfactant. The synthetic produced water was prepared in a bench scale and the region of interest in the diagram for the removal of metals was determined by experimental design called. Ten points located in the phase Winsor II were selected in an area with a large amount of water and small amounts of reagents. The samples were analyzed in atomic absorption spectrometer, and the results were evaluated through a statistical assesment, allowing the efficiency analysis of the effects and their interactions. The results showed percentages of extraction above 90% for the metals manganese, iron, chromium, calcium, barium and magnesium, and around 45% for metals lithium and potassium. The optimal point for the simultaneous removal of metals was calculated using statistical artifact multiple response function (MR). This calculation showed that the point of greatest extraction of metals occurs was the J point, with the composition [72% AP, 9% OP, 19% C/S], obtaining a global extraction percentage about 80%. Considering the aspects analyzed, the microemulsioned system has shown itself to be an effective alternative in the extraction of metals on synthetic produced water remediation